Impact of Teacher’s Pupil’s Class Relationship on Academics in Selected Schools of Bubare Town Council Rubanda District. - Sabiiti, Yosam (Kabale University, 2024)
This study investigated the impact of teacher-pupil relationships on academic performance within selected schools in Bubare Town Council, Rubanda District. The objectives include examining the quality and nature of teacher-pupil interactions, evaluating academic performance in relation to these relationships, and identifying factors that influence the dynamics between teachers and students. Utilizing both qualitative and quantitative methods, the research seeks to understand how positive and negative relationships affect student engagement, motivation, and overall academic outcomes. Previous studies have shown that strong teacher-student relationships are linked to higher academic achievement (Hamre & Pianta, 2001; Roorda et al., 2011). The findings aim to provide insights into the importance of fostering healthy teacher-pupil relationships to enhance educational success in Bubare Town Council schools. The study emphasizes the need for teacher training programs that focus on relationship-building and communication skills, aligning with the recommendations of the National Education Association (2018), to create supportive learning environments conducive to academic achievement.